Treatment of high-grade acetabular defects: Do porous titanium cups provide better stability than traditional titanium cups when combined with an augment? - Beckmann, Nicholas A.; Bitsch, Rudi G.; Klotz, Matthias C. M.; Bruckner, Thomas; Jäger, Sebastian (The journal of arthroplasty, 2018)
Background - Revision total hip arthroplasty frequently faces challenges associated with deficient bone stock. Porous metal implants were developed to meet the challenge, but require rapid osseointegration for ultimate success. This study aims to assess relative motion as an indicator for primary stability and osseointegration of two different titanium cups each combined with a titanium augment. - Methods - In 14 cadaver hemipelvises, 2 types of titanium acetabular cups, a traditional sintered-bead cup (POROCOAT Acetabular Cup [PAC]) and a newer porous-coated cup (GRIPTION Acetabular Cup [GAC]) each associated with a porous augment, were subjected to 3-dimensional varying loads, replicating 30% of loads experienced during normal gait. Relative motion was measured at the cup/bone, augment/bone, and cup/augment interfaces. - Results - Only at the cup/bone interface was there a statistically significant difference in relative motion between the traditional PAC and the newer GAC, with PAC showing less relative motion (P = .0037). Bone mineral density (BMD) had a significant effect on relative motion (P = .0019) at the cup/bone interface of both cup types, with low BMD specimens showing more relative motion. - Conclusion - Both cup types combined with augments displayed minimal relative motion that was within the accepted range thought to allow osseointegration, although the traditional surface proved superior to the newer surface. This difference was more pronounced at low BMD, with the well-established PAC cup displaying less relative motion than the more porous GAC cup, consistent with better osseointegration than the more porous cup. This suggests that the more porous implant may be less advantageous than traditional PAC cups, particularly in cases with poorer bone stock.